Agriculture & Tourism – Partners in Development” - Inter-American Institute for Cooperation on Agriculture (Inter-American Institute for Cooperation on Agriculture, 2006)
The major objectives of the workshop were to share and exchange Best Practices and success stories in Agro-tourism in the Caribbean, with a view to preparing a strategy and programme for the development and promotion of agro-tourism in the Region...